RELAÇÃO ENTRE O PRIMEIRO GOL E O RESULTADO FINAL DO JOGO DE FUTSAL NA COPA DO MUNDO DE 2012 - Werlayne Stuart Soares Leite (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Among the many technical and tactical aspects of players behavior, the goals are the most studied. It is true that the goal is the key of success for the teams and therefore its analysis in all matches in a big futsal tournament (world cup) allows for multiple assessments. The objective of this study was to analyze the first goal impact to the result in a futsal match, identifying the team that scored the first goal of the match and the result obtained by this team: win, draw or lose. Subsequently, relate the obtained results with physical, technical, tactical and psychological performance. We analyzed all the matches in World Cup 2012 (n=52). The data were obtained from the database of the website of the Fédération Internationale de Football Association - FIFA through official overviews of the matches. We collected quantitative data, which are related to the time the goals were scored in the course of the matches. According to the data obtained, the team that scored the first goal of the match won in 71.15% of the matches, with a high probability of winning. This high probability should be associated to the physical, technical, tactical and mainly psychological aspect.